Lipid Adaptations against Oxidative Challenge in the Healthy Adult Human Brain - Mariona Jové; Natàlia Mota-Martorell; Èlia Obis; Joaquim Sol; Meritxell Martín-Garí; Isidre Ferrer; Manuel Portero-Otín; Reinald Pamplona (MDPI AG, 2023)
It is assumed that the human brain is especially susceptible to oxidative stress, based on specific traits such as a higher rate of mitochondrial free radical production, a high content in peroxidizable fatty acids, and a low antioxidant defense. However, it is also evident that human neurons, although they are post-mitotic cells, survive throughout an entire lifetime. Therefore, to reduce or avoid the impact of oxidative stress on neuron functionality and survival, they must have evolved several adaptive mechanisms to cope with the deleterious effects of oxidative stress. Several of these antioxidant features are derived from lipid adaptations. At least six lipid adaptations against oxidative challenge in the healthy human brain can be discerned. In this work, we explore the idea that neurons and, by extension, the human brain is endowed with an important arsenal of non-pro-oxidant and antioxidant measures to preserve neuronal function, refuting part of the initial premise.